Financial Issues - Martie Gillen; Josephine Turner (EDIS)
Although we cannot foresee unexpected events, planning can help us control some financial issues that may arise. This revised 4-page fact sheet highlights the main financial problems older adults face during retirements, and solutions to help plan and manage a successful retirement. Written by Martie Gillen and Josephine Turner, and published by the UF Department of Family, Youth and Community Sciences, November 2012.